Partial urorectal septum malformation sequence with prune belly syndrome and oesophageal atresia with a tracheoesophageal fistula - N.Z. Mashavave; D.S. Harrison; A.D. Grieve (Elsevier, 2019)
The concurrence of Urorectal Septum Malformation (URSM) Sequence and Prune Belly Syndrome are extremely uncommon, with increased rarity with the coexistence of an oesophageal atresia with tracheoesophageal fistula. The URSM is denoted by an absence of perineal/anal orifices together with ambiguous genitalia, urogenital, colorectal and lumbosacral anomalies. A persistent cloaca or a partial URSMS entails a single anal/perineal opening that drains the urethra, vagina and rectum. Prune belly syndrome (PBS) encompasses the triad of urological connective tissue anomalies, absence or weakened abdominal walls, and cryptorchidism. In patients that do not fulfil the complete criteria a term pseudo-prune belly syndrome (PPBS) is used. The Prune belly spectrum is associated with poor prognosis due to pulmonary and renal complications. We discuss a rare case of a neonate with pseudo-prune belly syndrome, partial urorectal septum malformation and oesophageal atresia with tracheoesophageal fistula. Keywords: Partial urorectal septum malformation sequence (URSMS), Cloaca, Prune belly syndrome, Oesophageal atresia/tracheoesophageal fistula